Anais Do XXIII Workshop De Informática Na Escola (WIE 2017) 2017
DOI: 10.5753/cbie.wie.2017.795
|View full text |Cite
|
Sign up to set email alerts
|

Pensamento computacional sob a perspectiva de licenciandos em computação

Abstract: Resumo. A literatura da área de Educação em Computação aponta para a necessidade de integrar o Pensamento Computacional (PC) no currículo escolar, tendo os estudantes uma compreensão dos fundamentos da Ciência da IntroduçãoEm um mundo cada vez mais tecnológico, é necessário que os estudantes tenham um claro entendimento dos princípios e práticas da Ciência da Computação (CC), independente de seus campos de estudo e atuação (CSTA, 2011). O acesso ao conhecimento dos fundamentos de CC pode auxiliar a utilizar te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 3 publications
0
9
0
4
Order By: Relevance
“…França and Tedesco [15] found that the CS student teachers interviewed presented a good understanding of CT. However, it is important to note that the first author of this paper was an instructor in the program and of these students, which probably reflected on their achievement on this specific theme.…”
Section: Table 1: Publications On Computational Thinking and Teacher mentioning
confidence: 94%
See 4 more Smart Citations
“…França and Tedesco [15] found that the CS student teachers interviewed presented a good understanding of CT. However, it is important to note that the first author of this paper was an instructor in the program and of these students, which probably reflected on their achievement on this specific theme.…”
Section: Table 1: Publications On Computational Thinking and Teacher mentioning
confidence: 94%
“…From the 13 papers retrieved in our manual search on CT and teacher development, eight present research with schoolteachers [3,6,10,22,24,25,30,32], and five developed research in higher education [2,13,14,15,19 schoolteachers Souza et al [32] 2016 WAlgProg Costa et al [10] 2017 WAlgProg Leite et al [22] 2017 WAlgProg Silva et al [30] 2017 WIE Martinelli et al [24] 2018 WIE Martinelli and Sakata [25] 2018 WIE Barros et al [6] 2018 SBIE…”
Section: Figure 1: Number Of Publications With "Computational Thinkinmentioning
confidence: 99%
See 3 more Smart Citations